Ecophysiological studies of Citrullus colocynthis in response to spatial and seasonal changes in Wadi Al-Akhder, Tabuk Region, Saudi Arabia - SALEM MESFIR AL-QAHTANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Al-Qahtani SM. 2023. Ecophysiological studies of Citrullus colocynthis in response to spatial and seasonal changes in Wadi Al-Akhder, Tabuk Region, Saudi Arabia. Biodiversitas 24: 3292-3299. In order to achieve stress tolerance of Citrullus colocynthis (C. colocynthis), the soil physicochemical properties and chemical composition of plants in response to spatial and seasonal changes were investigated in Wadi Al-Akhder, Tabuk region, Saudi Arabia. The ANOVA results showed significant differences in studied factors for soil physicochemical properties and chemical composition of C. colocynthis. Soil pH was observed to range between neutral and slightly alkaline in the study region. Most soil physicochemical properties and most chemical composition extracted from C. colocynthisplants collected from Wadi Al-Akhder in the upstream and midstream sites were significantly increased compared with other stream sites, respectively. Most physicochemical properties of the soil supporting C. colocynthis significantly increased during the upstream sites 20-40 depth. In winter, C. colocynthis showed higher contents of mineral compositions (nitrogen, calcium, magnesium, sodium and potassium), photosynthetic pigments, moisture content percentage, and chemical compositions including ash, crude fiber, crude protein, and carbohydrate contents compared to those in summer while the opposite was found in the case of phosphorus and proline contents. Most chemical compositions extracted from C. colocynthis were greater in the winter season than in the summer season in the downstream site. During the desert environment, C. colocynthis plants tend to metabolic adaptation and resistance to external stress by accumulating osmolytes such as phosphorus, calcium, total pigment, and proline.